Pengaruh Model Pembelajaran Reading, Mind Mapping, dan Sharing Berbantuan Media Flipbook terhadap Kemampuan Literasi Digital pada Mata Pelajaran Biologi Siswa Kelas XI SMA Negeri 11 Samarinda - Syarifah Aisyah Anugrah Syam; Vandalita Maria Magdalena Rambitan; Akhmad Akhmad; Nelda Anasthasia Serena (Biocaster : Jurnal Kajian Biologi, 2026)
Monotonous learning makes students accustomed to receiving information without searching, evaluating, and processing information independently. This condition has an impact on students' low digital literacy skills. Digital literacy skills are students' abilities to access, understand, evaluate, and use digital information to support the learning process. One effort that can be done is to apply various methods and media in the learning process. A model that can meet these needs is the Reading, Mind Mapping, and Sharing (RMS) learning model. This study aims to examine the effect of implementing the RMS learning model assisted by flipbook media on digital literacy skills in biology subjects of grade XI students of SMAN 11 Samarinda. This study uses a quantitative method using a nonequivalent control group pretest-posttest design with a purposive sampling technique and a sample of 50 students. The instrument analysis technique used is the expert validation test, while the data analysis technique used is the N-Gain test and the independent sample t-test. The N-Gain test of the digital literacy questionnaire in the experimental class was 0.3 with a medium category, while in the control class it was 0.02 with a low category. Furthermore, the results of the independent sample t-test on the digital literacy questionnaire showed a p-value <0.001. Thus, it can be concluded that the flipbook-assisted RMS learning model has an effect on digital literacy skills in biology among eleventh-grade students at SMAN 11 Samarinda. These findings indicate that the flipbook-assisted RMS model is effective in improving students' digital literacy skills through reading activities, concept mapping, and collaborative information sharing.